Effects of land tenure on soil and water conservation measures in Tanzania?s Kigoma Region - Dekenah, Tamsyn (School of Economics, 2025)
Environmental challenges brought on by climate change, such as soil erosion, pose a threat to the livelihoods of small-scale farmers across Africa. Land security may encourage these farmers to invest in soil and water conservation (SWC) measures, which can combat land degradation, and consequently improve plot productivity. Studies on the nexus between land tenure and SWC measures in Africa are rare and have yielded mixed results. This paper examines the relationship between land tenure and the use of SWC measures in Tanzania's Kigoma region. The conservation measures investigated are as follows: mulching, ridging, terracing, stone or soil bunds, and tree planting. Land tenure is measured by whether participants hold a Certificate of Customary Right of Occupancy (CCRO). A heteroskedastic probit model shows that CCROs are significantly, positively associated with tree planting. This demonstrates that a stronger land tenure programme can increase the use of long-term SWC measures on small-scale farms in Tanzania.